MAPPING VALUE ADDED ARABICA COFFEE PROCESSED PRODUCTS IN ACEH TENGAH - Fadli, Fadli; Tambarta Kembaren, Emmia; Sinta, Irada (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
Coffee is one of the plantation commodities that has an important role in foreign trade. In 1712, Indonesian coffee plantations were traded for the first time to the Netherlands (KP Gayo, 2016). Aceh coffee, which is better known internationally is the type of Gayo Arabica coffee because it has a distinctive aroma and taste. This research uses descriptive quantitative research methods. This research was conducted in Aceh Tengah. This is because Aceh Tengah is one of the main production Aceh Tengah. The objects of this research are the trade office, the agriculture office, coffee expert staff, Gayo arabica coffee farmers and the four green been coffee agroindustry and coffee grounds which have the largest export quotas in Bener Meriah Regency, namely KBQ Baburrayyan, Oro Coffee Cooperative, and PT Olam Coffee. The data collection method used is in-depth interviews with several key persons belonging to the research object. The results showed that the output value obtained from pumpkin coffee products was Rp. 27,176 per Kg with an added value of Rp. 22,176 per Kg. The output value obtained from green bean products is Rp. 56,950/Kg with an added value of Rp. 13,050/Kg. The output value obtained from the Gayo Arabica coffee powder product is Rp. 123.500/Kg with an added value of Rp. 36.500/Kg. 176 per Kg with an added value of Rp. 22,176 per Kg. The output value obtained from green bean products is Rp. 56,950/Kg with an added value of Rp. 13,050/Kg. The output value obtained from the Gayo Arabica coffee powder product is Rp. 123.500/Kg with an added value of Rp. 36.500/Kg. 176 per Kg with an added value of Rp. 22,176 per Kg. The output value obtained from green bean products is Rp. 56,950/Kg with an added value of Rp. 13,050/Kg. The output value obtained from the Gayo Arabica coffee powder product is Rp. 123.500/Kg with an added value of Rp. 36.500/Kg.